Organizational readiness, management support, financial technology, and accounting information systems for supply chain performance: Insights from Islamic economics - Hasibuan, Reni Ria Armayani; Hayati, Fitri; Nurhayati, Nurhayati (Journal of Islamic Economics Lariba, 2026)
IntroductionMicro, small, and medium enterprises play a vital role in economic growth, employment generation, and regional development. However, increasing digitalization and supply chain complexity require these enterprises to strengthen organizational capabilities and integrate digital technologies to improve operational performance. Although organizational readiness, management support, financial technology, and accounting information systems have received growing scholarly attention, their integrated effects on supply chain performance remain insufficiently understood, particularly in emerging economies.ObjectivesThis study examines the effects of organizational readiness, management support, and financial technology adoption on supply chain performance while investigating the mediating role of accounting information systems. It also develops an integrated theoretical framework by combining organizational capability and digital transformation perspectives with insights from Islamic economics.MethodThis study employed a quantitative explanatory research design involving 396 micro, small, and medium enterprises operating in Medan, Indonesia. Data were collected through structured questionnaires administered to business owners and managers and analyzed using Structural Equation Modeling based on Partial Least Squares. The analysis evaluated measurement reliability and validity, structural relationships, and mediation effects among the proposed constructs.ResultsThe findings demonstrate that organizational readiness, management support, and financial technology adoption significantly improve accounting information systems and supply chain performance. Financial technology adoption exhibits the strongest influence on accounting information systems, while accounting information systems significantly enhance supply chain performance and mediate the effects of organizational readiness, management support, and financial technology adoption. These results indicate that successful digital transformation depends not only on technological adoption but also on organizational preparedness, leadership commitment, and integrated information systems that improve decision-making, operational coordination, and supply chain efficiency.ImplicationsThe findings suggest that managers should implement integrated digital transformation strategies by strengthening organizational readiness, leadership commitment, financial technology utilization, and accounting information systems simultaneously. Policymakers should support these efforts through digital infrastructure development, managerial capability enhancement, financial inclusion initiatives, and regulatory frameworks that facilitate sustainable digital transformation among micro, small, and medium enterprises.Originality/NoveltyThis study contributes to the digital transformation literature by integrating the Resource-Based View, the Technology–Organization–Environment framework, Dynamic Capabilities Theory, and the DeLone and McLean Information Systems Success Model into a unified framework explaining supply chain performance. It further enriches existing knowledge by incorporating Islamic economics perspectives that emphasize transparency, justice, financial inclusion, and ethical digital governance as complementary foundations for sustainable organizational performance.